Situational Leadership in Facing Digital Transformation in the Industrial 4.0 Era: in Improving Teacher Performance - Tiara Dofinsa; Riza Restu; Nurhizrah Gistituati; Anisah; Rusdinal (Mudir: Jurnal Manajemen Pendidikan, 2025)
This study employs a qualitative method with a literature review approach to gain an in-depth understanding of situational leadership in responding to the challenges of digital transformation in the Industry 4.0 era. The approach involves examining relevant literature sources such as books, scientific articles, and journals related to leadership concepts, particularly situational leadership, as well as the role of school principals as leaders in educational settings. Data analysis is conducted qualitatively through stages of data reduction, information selection, synthesis, and interpretation of theoretical perspectives and relevant empirical findings. Information is categorized based on key themes such as technology adaptation, the role of school principals as change agents, and the development of teacher competencies in the digital era. The results of this study are expected to provide a comprehensive understanding of the importance of situational leadership in enhancing teacher performance amid the continuously evolving dynamics of education.